Bioprospecting and Characterization of poly-Î²- hydroxyalkanoate (PHAs) producing Pseudomonas Spp. isolated from edible oil contaminated soil - Marjadi, Darshan; Dharaiya, Nishith (Research in Biotechnology, 2012)
Plastics have battle to biological breakdown that result in its accumulation in the environment. This accentuates the need to search for biodegradable polymer, which is readily disposable and degradable. Bacteria synthesize and accumulate polyhydroxy alkanote (PHA) as carbon source under limiting conditions of nutrients. Bioprospecting for poly-Î²-hydroxyalkanoate (PHA)-accumulating micro-organisms was carried out in edible oil contaminated soil of north Gujarat region. They were isolated in unbalanced culture medium (high carbon/nitrogen ratio) with various edible oil used as carbon source. PHAs producing bacteria were identified by staining with Sudan black and solubilising cellular components in sodium hypochlorite. Two bacterial strains isolated, screened and characterized from edible oil contaminated soil samples were selected due to their capacity of growing in the presence of edible oil and at the same time producing PHA. The isolates were identified by PCR of the 16S rDNA gene using universal primers. The isolates were Psudomonas aeruginosa and Pseudomonas fluorescence.